Economic Policy in the Context of Improving the Development of Corporate Governance. - Алексеєнко Людмила Михайлівна, Alekseyenko Lyudmyla; Тулай Оксана Іванівна, Tulai Oksana (Східноєвропейський національний університет імені Лесі Українки., 2020)
The National Securities and Stock Market Commission of Ukraine is implementing a phased process of adapting of conditions of national trading systems to the EU rules to achieve greater transparency in the market. In the process of comprehensive reform of the rules and conditions of organised trade a special attention is payed to: to improve the activities of stock exchanges and settlement procedure of admission of securities of the issuer to the stock exchange; to establish new requirements for trading systems, cyber protection and implementation of the corporate governance of exchanges; the changing the rules of reports on OTC transactions; the introduction of restrictive measures, in particular the ban on the use of economic entities in their activity of electronic trading systems “the Plaza software” and “Forts software”; the introduction of new terms “before sessional period” and “after sessional period” instead of the term “trading session” that will allow stock exchange to divide trading day for the relevant periods and the trading session for the submission of applications for the purchase and sale of securities, other financial instruments and to conclude exchange contracts for such applications, including with the participation of a market maker.
Keywords: stock market; cyber protection; comprehensive reform; corporate governance; stock exchange; corporate sector